Ionicity of ZnO —A key system for transparent conductive oxides. (24th August 2018) - Schmeißer, Dieter; Henkel, Karsten; Janowitz, Christoph
Abstract: The electronic structure of ZnO is dominated by coexisting electron and ionic states/bonds caused by charge polarization and self-trapping phenomena of the valence charges. Their interplay manifests itself in intrinsic electronic defects which have different degree of spatial localization and electronic correlation. The relative abundance of intrinsic defects can be determined by the ionicity factor and its value can be derived from three independent experimental procedures in a consistent way. This approach also explains the complex satellite features in the XPS and XAS data. Ionicity and satellite formation are two experimental findings which can be explained consistently in the same context of mixed-atomic valence states and intrinsic electronic defects.